Design of a Campaign for the Use of Sustainable Fashion Products as a Supporting Program for the Exhibition at Upject ID - Moch Ahya Fatihun Arif; Nanda Nini Anggalih (Universitas Negeri Surabaya, 2026)
Fast fashion has become one of the major contributors to textile waste due to high clothing consumption, short product life cycles, and limited public awareness of its environmental impact. This project aims to design a visual campaign that promotes sustainable fashion through Upject ID as an educational and participatory medium for young audiences. The design process employed a visual communication design approach, consisting of research, audience and media analysis, development of communication and visual concepts, content planning, media prototyping, and initial testing. The campaign was developed using a contemporary minimalist visual style with raw organic elements that reflect the characteristics of upcycled denim materials. The resulting campaign media include an upcycle donation box, brochures, flyers, hang tags, and Instagram content as supporting media for the exhibition. Initial testing showed that the campaign was able to communicate the message clearly and attractively, encourage audience interaction, and increase interest in sustainable fashion practices. This project demonstrates that an exhibition-based visual campaign can function not only as a promotional tool but also as an educational medium that supports awareness and participation in responsible fashion consumption.